2015
DOI: 10.1590/0100-3984.2014.0072
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between Hashimoto’s thyroiditis and thyroid cancer? A retrospective data analysis

Abstract: ObjectiveTo evaluate the association between Hashimoto's thyroiditis (HT) and papillary thyroid carcinoma (PTC).Materials and MethodsThe patients were evaluated by ultrasonography-guided fine needle aspiration cytology. Typical cytopathological aspects and/or classical histopathological findings were taken into consideration in the diagnosis of HT, and only histopathological results were considered in the diagnosis of PTC.ResultsAmong 1,049 patients with multi- or uninodular goiter (903 women and 146 men), 173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…There were also significant differences in the patient population of FNA studies. The inclusion criteria of FNA studies included consecutive patients [ 23 , 28 ], patients with benign thyroid diseases [ 26 ], patients with cold thyroid nodules [ 8 ], patients with nodules ≥ 10 mm [ 21 ], and patients with nodules ≥ 5 mm and aged ≥ 18 years [ 4 ]. This may be one explanation for the wide incidence range of PTC, from 0.12% to 20.87%.…”
Section: Discussionmentioning
confidence: 99%
“…There were also significant differences in the patient population of FNA studies. The inclusion criteria of FNA studies included consecutive patients [ 23 , 28 ], patients with benign thyroid diseases [ 26 ], patients with cold thyroid nodules [ 8 ], patients with nodules ≥ 10 mm [ 21 ], and patients with nodules ≥ 5 mm and aged ≥ 18 years [ 4 ]. This may be one explanation for the wide incidence range of PTC, from 0.12% to 20.87%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are some contradictory data; Selek et al and de Alcantara-Jones et al [12,22,23] reported no difference in the prevalence of lymphocyte infiltration or anti-thyroid antibodies between thyroid cancer group and benign tumor group.…”
Section: Studies With Surgical Specimensmentioning
confidence: 98%
“…Controversial results were also reported in population-based studies of thyroid nodules by FNAC. Some studies reported an association between HT and TC [4,6,8], whereas others did not [25][26][27][28][29][30][31]. Possible sources of bias in Boi's [6] and Fiore's [4,28] studies were discussed previously [25].…”
Section: Table IV or In This Table Evaluates The Ratio Of Malignancymentioning
confidence: 99%